TAMAN PINTAR PELAIHARI - Muhammad Haris Fadillah; Dahliani Dahliani (ULM Press, 2021)
Pelaihari Smart Park is a park that designed to accommodate tourism and learning activities at the same time, smart parks have been widely applied in big cities in Indonesia, therefore many people decide to travel to smart parks, besides being fun, smart parks also provide useful knowledge , Pelaihari is a city that has many tourist attractions ranging from mountains to beaches, but the tourist attractions that are owned are just fun places, there are no tourist attractions that can develop people's interest in learning, so a smart park is designed in the city of Pelaihari, with a recreational and creative approach. Educative people will be presented with a variety of fun tourist objects that can provide experience and knowledge simultaneously, with this method it is hoped that people's interest in learning can increase and change perspectives if learning is not boring.